Analisis Potensi, Efektivitas, dan Efisiensi Penerimaan Retribusi Pelayanan Persampahan/Kebersihan di Kabupaten Lombok Barat Tahun 2019-2023 - Chandra Wardani; Siti Sriningsih; Ali Akbar Hidayat (Economic Reviews Journal, 2025)
This study aims to determine the extent of revenue from waste management/sanitation services in West Lombok Regency from 2019 to 2023. This study employs a quantitative descriptive approach as the analytical model to examine how potential, effectiveness, and efficiency strongly correlate with the level of waste management/sanitation service fees in West Lombok Regency from 2019 to 2023. The results of the analysis indicate that the potential for waste management/cleaning service fees falls into the prime category and serves as a key sector for the West Lombok Regency government. Additionally, the analysis of effectiveness levels revealed an average of 109% for waste management and cleaning service fee revenue, thereby meeting the criteria for highly effective performance. Furthermore, the efficiency analysis over the past five years showed a very high level of efficiency in waste management and sanitation service fee revenue for West Lombok Regency. According to the trend projection analysis, the estimated waste management and sanitation service fee revenue for West Lombok Regency over the next four years indicates a trend toward increase or a positive trend.